1999
DOI: 10.1002/pdi.1960160404
|View full text |Cite
|
Sign up to set email alerts
|

The detection of pedal osteomyelitis in diabetic patients

Abstract: Pedal osteomyelitis in diabetic patients is a serious clinical problem. There is no single, reliable diagnostic tool; plain films are inaccurate, bone scans nonspecific and the role of human pooled immunoglobulin (Hig) scans remains unclear. Magnetic Resonance Imaging (MRI) may prove useful. We therefore aimed to compare these four diagnostic modalities. Thirteen diabetic patients with possible pedal osteomyelitis were recruited. Nine were found to have osteomyelitis based on clinical, microbiological, and sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The prevalence of standard defined osteomyelitis was 50% (range 32% to 89%), the pooled sensitivity was 77–100% and the specificity was 40–100%. In subjects with diabetes, the diagnostic odds ratio was 42 (CI 15–120), the summary positive likelihood ratio was 3.8 (CI 0.2.5–5.8) and the summary negative likelihood ratio was 0.14 (CI 0.08–0.26) . More recently performed studies reported lower diagnostic odds ratios (25, CI 6–117) compared with older ones, perhaps because their study designs were better.…”
Section: Diagnosismentioning
confidence: 94%
See 1 more Smart Citation
“…The prevalence of standard defined osteomyelitis was 50% (range 32% to 89%), the pooled sensitivity was 77–100% and the specificity was 40–100%. In subjects with diabetes, the diagnostic odds ratio was 42 (CI 15–120), the summary positive likelihood ratio was 3.8 (CI 0.2.5–5.8) and the summary negative likelihood ratio was 0.14 (CI 0.08–0.26) . More recently performed studies reported lower diagnostic odds ratios (25, CI 6–117) compared with older ones, perhaps because their study designs were better.…”
Section: Diagnosismentioning
confidence: 94%
“…On the basis of seven studies, Kapoor et al . found the performance characteristics of a triple‐phase bone scan were markedly inferior to MRI , with a diagnostic odds ratio of 3.5 (CI 1.0–13) versus 150 (CI 55–411), respectively . Healthy bone may also have an increased uptake of the radiopharmaceutical, especially in the forefoot .…”
Section: Diagnosismentioning
confidence: 99%
“…Dinh and coworkers (170) identified four trials, all of which had a prospective setup (180,182,195,199). Kapoor et al (198) found 16 trials in their meta-analysis (171,172,180,182,188,192,195,196,(200)(201)(202)(203)(204)(205)(206)(207). Only one study was conducted for less than 10 years (195).…”
Section: Radiological Studies-magnetic Resonance Imagingmentioning
confidence: 99%
“…Bone scans are usually performed with 99m Tc-methylene diphosphate. Seven studies were found by Kapoor et al (198) that compared MRI with triplephase bone scan (171,182,188,192,202,206,207). Capriotti et al found in a total of 719 lesions that three-phase bone scans were sensitive (90%) but not specific (46%) (208).…”
Section: Radiological Studies-nuclear Medicinementioning
confidence: 99%